BUSINESS DEVELOPMENT ANALYSIS OF BUSINESS MODEL CANVAS (BMC) AND SWOT IN WEST BEKASI COFFEE INTERMEDIARY UMKM - Ida Hendarsih; Amas Sari Martanti; Diana Tambunan (CV. RADJA PUBLIKA, 2025)
Coffee Intermediary Business as an MSME business still needs optimization for business development. The purpose of this study is to analyze the canvas business model and SWOT analysis to provide business improvements in Coffee Intermediary MSME. The analysis method used in the study is descriptive qualitative, while the data analysis technique used is BMC (Business Model Canvas). The data used includes primary and secondary data. The results of the study indicate that the Coffee Intermediary MSME business model needs to be improved in the elements of key partners, key activities, key resources, revenue streams, while the results of the SWOT analysis showed high scores on IFE (4.22) and EFE (4.33), indicating a strong competitive position with significant market opportunities, but to maintain its business excellence, Coffee Intermediary must continue to improve its strengths and improve its weaknesses.